Inflation in Pakistan : Money or Wheat? - Khan, Mohsin (IMF Working Papers; Working Paper, 2006)
This paper examines the relative importance of monetary factors and structuralist supply-side factors for inflation in Pakistan. A stylized inflation model is specified that includes standard monetary variables (money supply, credit to the private sector), the exchange rate, as well as the wheat support price as a supply-side factor that has received considerable attention in Pakistan. The model is estimated for the period January 1998 to June 2005 on a monthly basis. The results indicate that monetary factors have played a dominant role in recent inflation, affecting inflation with a lag of about one year. Changes in the wheat support price influence inflation in the short run, but not in the long run. Furthermore, the wheat support price matters only over the medium term if accommodated by monetary policy.